Social inequalities in alcohol consumption in the Czech Republic: a multilevel analysis - Dzúrová, Dagmara; Spilková, Jana; Pikhart, Hynek (Health & place, 2010)
Czech Republic traditionally ranks among the countries with the highest alcohol, consumption. This paper examines both risk and protective factors for frequent of alcohol, consumption in the Czech population using multilevel analysis. Risk factors were measured at the, individual level and at the area level. The individual-level data were obtained from a survey for a, sample of 3526 respondents aged 18-64 years. The area-level data were obtained from the Czech, Statistical Office. The group most inclinable to risk alcohol consumption and binge drinking are mainly, men, who live as single, with low education and also unemployed. Only the variable for divorce rate, showed statistical significance at both levels, thus the individual and the aggregated one. No cross-level interactions were found to be statistically significant.
Keywords: logistické modely; Alcoholism; zdravotnické přehledy; Humans; lidé středního věku; Multivariate Analysis; Alcohol Drinking; pití alkoholu; Female; rizikové faktory; dospělí; lidé; Adult; společenská třída; analýza malých oblastí; ženské pohlaví; multivariační analýza; Male; chudé oblasti; Middle Aged; Adolescent; alkoholismus; Czech Republic; Small-Area Analysis; Health Surveys; Social Class; Česká republika; mužské pohlaví; Poverty Areas; Logistic Models; mladiství; Risk Factors